The Message or the Channel: An Experimental Design of Consumers' Perceptions of a Local Food Message and the Media Channels Used to Deliver the Information - Jessica Holt; Joy N. Rumble; Ricky Telg; Alexa Lamm (Journal of Applied Communications, 2015)
With the ever-increasing options of communication media channels, the question of, “Which media channel is the best for a message?” is an important question for researchers and professionals in the agricultural arena. This research sought to determine how the interaction between consumers’ perceptions of the message and past media use impacted their attitudes toward the media channels of print, video, and Web. The theoretical framework used in this study was media richness, which was used to understand the characteristics of different media channels and their ability to deliver information. The message used in this study was related to buying local food in Florida. This study used an experimental design to assess respondents’ attitudes toward media channels. The population for the study was Florida consumers, and a non-probability sample was used. The 1,122 respondents’ of this study were given a message through one of the three media channels of a print, video, or Web advertisement and then asked their perceptions of the message and the media channel. The results indicated respondents’ attitudes toward the channel were significantly impacted by their perception of the message but not their past media usage. Recommendations for future research of theory and professional application are given.
Keywords: Attitude toward media channels; message perceptions; media richness; media channel perceptions; past media use; agricultural messages; local food messages; Association for Communication Excellence Conference